Review Article about Laser and its Applications - Hasson, Murtadha Salim Othman (American Journal of Botany and Bioengineering, 2025)
Laser technology has revolutionized various fields, from medicine to industry, due to its precision, coherence, and high energy efficiency. Despite extensive research, challenges remain in optimizing laser applications for medical treatments, industrial manufacturing, and scientific advancements. This review explores different types of lasers, their working principles, and their diverse applications, including spectroscopy, optical tweezers, surgery, and telecommunications. Through an analysis of recent developments, findings indicate that laser-based technologies continue to enhance efficiency, accuracy, and safety across multiple disciplines. The results emphasize the growing significance of laser innovations in modern technology, highlighting the need for further research into advanced laser systems for improved performance and broader applications.